Introduction to the Heijkoop approach to challenging behaviour in ID - Heijkoop, Jacques; Clegg, Jennifer (2012)
The Heijkoop method is used widely in ID challenging behaviour services across Northern Europe; the lack of an English-language account has inhibited its uptake in the UK. The method is fundamentally experiential and aimed at understanding the ‘Who’ of the client to complement the objectified ‘What’ knowledge of standard diagnostics. It is conceptually grounded in developmental psychology, focusing on interpersonal relationships and intersubjectivity, in particular Daniel Stern’s combination of clinical and empirical perspectives on attachment and the emerging sense of self. This working paper is informed by 5 years’ clinical use in Nottingham of Discovery Awareness, a process of video-analysis that is the core instrument in Heijkoop’s approach. Heijkoop introduced and developed this during three separate week-long periods of service consultancy into two NHS Assessment and Treatment Units within Nottinghamshire Healthcare NHS Trust’s specialist service for adults with ID.